Generation Z at Work: Exploring the Link Between Work Stress and the Desire to Leave the Job with Job Satisfaction as a Mediating Variable - Nabila Syafira; Osly Usman (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study analyzes how the turnover intention among Generation Z workers was affected by their stress and their level of job satisfaction. A purposive sampling technique was used to obtain the data, and the data were gathered from 107 respondents using online questionnaires. The data analysis method used the Structural Equation Modeling-Partial Least Square (SEM-PLS) model from SmartPLS 4.0. The results show that Gen-Z employees’ work stress has a significant and negative effect on the level of their job satisfaction, so does the job satisfaction on their turnover intention. Work stress also plays a significant part on turnover intention by positively affecting it, while job satisfaction mediates this relationship.